1999
DOI: 10.1007/s100520050464
|View full text |Cite
|
Sign up to set email alerts
|

Hunting for contact interactions at HERA with polarized lepton and proton beams

Abstract: We explore the discovery and analysis potentials of the HERA collider, with and without polarized beams, in search for electron-quark contact interactions in the neutral current channel. We find that the sensitivity to contact interactions when both beams are polarized is similar to the unpolarized case, and is better than in the case where one has only lepton polarization. We emphasize that the measurement of spin asymmetries in such a polarized context could give some crucial informations on the chiral struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…So far, there is very little theoretical work in this direction. The only comprehensive studies of new physics searches in polarized hadronic collisions to date concern the effects of contact interactions [13,14] and of new gauge bosons [15] on spin asymmetries at RHIC and HERA. It was found that polarization information can yield vital insights, such as discriminating different types of contact interactions that yield identical signatures at unpolarized colliders.…”
Section: Introductionmentioning
confidence: 99%
“…So far, there is very little theoretical work in this direction. The only comprehensive studies of new physics searches in polarized hadronic collisions to date concern the effects of contact interactions [13,14] and of new gauge bosons [15] on spin asymmetries at RHIC and HERA. It was found that polarization information can yield vital insights, such as discriminating different types of contact interactions that yield identical signatures at unpolarized colliders.…”
Section: Introductionmentioning
confidence: 99%
“…According to our previous experience [7] we know that in general the Parity Violating (PV) two spin asymmetries exhibit stronger sensitivities to new chiral effects than the single spin asymmetries. Then we consider the case where the e and p (or neutrons) beams are both polarized.…”
Section: Polarized Casementioning
confidence: 99%
“…Some other observables, defined in [7], could be used to go further into the separation of the models. However the sensitivities of these asymmetries are rather weak, and they can be useful only for some particularly favorable values of the parameters (M,λ).…”
Section: Polarized Casementioning
confidence: 99%
See 1 more Smart Citation
“…Helicity-selected matrix elements have been theoretically obtained in LO not only for the standard model but also for the contact interaction. In case' of Drell-Yan process, corresponding matrix elements were obtained from Virey's calculation for DIS by crossing [8]. A weighted mean method is applied in order to extract spin asymmetries using "unpolarized" event generator PYTHIA.…”
Section: Introductionmentioning
confidence: 99%